Wrapped Up in the Cis-Tem: Trans Liveability in the Age of Algorithmic Violence - Andersen, Christoffer Koch (Atlantis)

(untitled) (Mount Saint Vincent University, 2025)
Algorithms pervade our reality and promise to universally enhance our lives, but what happens when this promise is reserved for cisgender people while subjecting trans people to legacies of anti-trans violence that implicate trans liveability? Despite this key question, existing critiques engage only sparingly with the violent legacies perpetuated by algorithms that trans people encounter, rarely go beyond notions of bias, and therefore fail to centre trans experiences. In this article, I extend scholarship on critical algorithm studies, trans studies, and necropolitics through three accounts of lived trans experiences to show the vicious algorithmic operations on trans lives. Centrally, this article argues that algorithms are not neutral, distinct, or progressive. Rather, as a vicious “cis-tem” (playing on the word system), algorithms enact forms of violence towards the possibility of transness, violence that is rooted in legacies of capitalist, colonial, and cisheteronormative power that violate trans lives and radicalise transphobia. Contrasting trans voices against the algorithmic machines, this article offers a novel perspective on the entanglement between algorithms and trans liveability through the lens of algorithmic violence. I demonstrate how algorithms embody racialised and gendered ideals of the human that target trans people through engineered transphobic feedback-loops, cisnormative default, and capitalist profit based on fear. I conclude by reimagining liberatory digital futures.